Factors of influence in the activity of titanocenes in the homogeneous catalysis of polymerization of polystyrene. - Pereira, BCD; Klein, S. I. (Editora Unesp, 2000)
It is presented a review with 42 references dealing with the historical aspects of organometallics of titanium, the application of titanocenes in catalytical systems and the factors that may influence in the polymerisation of alpha -olefinas with the consequent repercussions an the structures of the polymers.
Keywords: titanium cyclopentadienyls; homogeneous catalysis; polystyrene